2020
DOI: 10.1101/2020.04.03.023804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic evaluation of circulating proteins for drug target characterisation and precision medicine

Abstract: Circulating proteins are vital in human health and disease and are frequently used as biomarkers for clinical decision-making or as targets for pharmacological intervention. By mapping and replicating protein quantitative trait loci (pQTL) for 90 cardiovascular proteins in over 30,000 individuals, we identified 467 pQTLs for 85 proteins. The pQTLs were used in combination with other sources of information to evaluate known drug targets, and suggest new target candidates or repositioning opportunities, underpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Larger efforts in terms of sample size, such as those by the SCALLOP consortium (www.scallopconsortium.com), are underway to expand pQTL discovery. Their first results in over 30,000 individuals identified 467 pQTLs for 85 proteins from the Olink CVD-I panel [84]. Of note, these efforts will enable systematic evaluation of consistency between proteomic platforms and provide orthogonal validation of correct protein targeting, supported by pQTLs located in or around the protein coding gene, and help identify epitope effects.…”
Section: Beyond Prediction: Integration Of Genomics and Proteomics Tomentioning
confidence: 98%
“…Larger efforts in terms of sample size, such as those by the SCALLOP consortium (www.scallopconsortium.com), are underway to expand pQTL discovery. Their first results in over 30,000 individuals identified 467 pQTLs for 85 proteins from the Olink CVD-I panel [84]. Of note, these efforts will enable systematic evaluation of consistency between proteomic platforms and provide orthogonal validation of correct protein targeting, supported by pQTLs located in or around the protein coding gene, and help identify epitope effects.…”
Section: Beyond Prediction: Integration Of Genomics and Proteomics Tomentioning
confidence: 98%
“…Significant eQTLs are defined on either p-value or FDR thresholds based on the specific data source (see URLs) and we retrieved results from blood, brain or lung tissues. For the pQTL analysis, we used data from 90 cardiovascular genes of the SCALLOP Consortium 53 and followed their definition of significant pQTLs. They defined signals more than 1Mb away from the protein gene as trans-pQTLs, and signals that were closer than 1Mb as cis-pQTL 53 .…”
Section: Gene Prioritisationmentioning
confidence: 99%
“…The plasma proteome has received particular attention as it can capture a wide variety of proteins that are active in different biological processes, including but not limited to circulation 14 . The proteome is often dysregulated by diseases, and it is highly amenable for drug targeting 15,16 . A number of genetic studies have identified protein quantitative trait loci (pQTL), for plasma [15][16][17][18][19] as well as some other tissues [20][21][22] , and noted that pQTLs are enriched for GWAS associations across an array of complex traits [15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…The proteome is often dysregulated by diseases, and it is highly amenable for drug targeting 15,16 . A number of genetic studies have identified protein quantitative trait loci (pQTL), for plasma [15][16][17][18][19] as well as some other tissues [20][21][22] , and noted that pQTLs are enriched for GWAS associations across an array of complex traits [15][16][17][18][19][20][21] . Studies have used pQTLs as instruments in conducting Mendelian randomization (MR) analysis to identify causative proteins, and hence potential therapeutic targets, across diverse phenotypes [23][24][25] , including COVID-19 related outcomes 18 .…”
Section: Introductionmentioning
confidence: 99%